2013
DOI: 10.5089/9781484384046.001
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing: Evidence from Current Account Adjustment in Europe

Abstract: After the 2003-2007 economic boom, European countries with large pre-crisis current account imbalances are undergoing adjustments. Countries are adjusting at different paces and ways reflecting the source and magnitude of imbalances, availability of financing, competitiveness of the tradable sector and external environment. While emerging European countries with large pre-crisis imbalances and a fixed exchange rate regime have seen sharp current account adjustments and a rebound in growth, adjustment in the eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…Among these works, the econometric analysis of Atoyan et al (2013) found that fiscal consolidation was one of the elements that explained the post-crisis external adjustment in Southern European debtor economies, in line with our findings. Cheung et al (2010) panel analysis -using data up to 2008 and assuming homogenous coefficients-finds that in the first phase of the crisis a large share of current account adjustment was due to cyclical factors, at least for the main economies.…”
Section: Introductionsupporting
confidence: 79%
“…Among these works, the econometric analysis of Atoyan et al (2013) found that fiscal consolidation was one of the elements that explained the post-crisis external adjustment in Southern European debtor economies, in line with our findings. Cheung et al (2010) panel analysis -using data up to 2008 and assuming homogenous coefficients-finds that in the first phase of the crisis a large share of current account adjustment was due to cyclical factors, at least for the main economies.…”
Section: Introductionsupporting
confidence: 79%
“…Focusing on sectorial savings and investment, Atoyan et al (2013) find important cross-country differences in current account developments. The authors investigate current account developments in Europe, with a comparative focus on the euro area periphery and emerging European countries with fixed exchange rate regimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current account deficits of these countries reached 25% of G.D.P. in the run-up to the financial crisis (Atoyan, Manning, KEYWORDS current account balance; price competitiveness; fiscal balance; capital inflow; panel vaR & Rahman, 2013). The overall trend has seen the advanced countries as net exporters and the periphery and emerging countries as net importers.…”
Section: Introductionmentioning
confidence: 99%
“…On the case of peripheral Eurozone countries (Italy, Spain, Greece, and Ireland), Atoyan et al (2013) came to the empirical evidence confirming that the main determinants of the CA during the boom before the recession in 2008 were cyclical factors: a large capital inflow, high credit activity, and low unemployment. The estimated coefficients with these variables are statistically significant and had expected signs: large capital inflows, high annual credit growth, and low employment that affected the CA deficit.…”
Section: Literature Reviewmentioning
confidence: 99%